Does venture capital investment really require spatial proximity? An empirical investigation - Michael Fritsch; Dirk Schilder (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2006)
We examine the role of spatial proximity for Venture Capital (VC) investments in Germany. The main database is a survey of 85 personal interviews with representatives of different types of financial institutions. The analysis shows that spatial proximity is far less important for VC investments than is often believed. For example, the results indicate that syndication is partly used as an alternative to spatial proximity. Telecommunication does not work as a substitute for face-to-face contact. On the whole, regional proximity is not a dominant factor in VC partnerships. Therefore, the absence of VC firms in a region does not appear to cause a severe regional equity gap.
Keywords: G24; O16; D21; M13; R12; 330; Venture Capital; spatial proximity; start-up financing